Mexico Energy Efficiency Report - ABB (ABB, 2012)

Mitigation Opportunities for Life-Cycle Greenhouse Gas Emissions during Feedstock Production across Heterogeneous Landscapes - Adler, P.R.; Del Grosso, S.J.; Inman, D.; Jenkins, R.E.; Spatari, S.; Zhang, Y. (Managing Agricultural Greenhouse Gasses: Coordinated agricultural research through GRACEnet to address our changing climate, 2012)

Measurements of Methane Emissions At Natural Gas Production Sites in the United States - Allen, D. T.; Torres, V. M.; Thomas, J.; Sullivan, D. W.; Harrison, M.; Hendler, A.; Herndon, S. C.; Kolb, C. E.; Fraser, M. P.; Hill, A. D.; Lamb, B. K.; Miskimins, J.; et al. (Proceedings of the National Academy of Sciences USA, 2013)
Keywords: Air Pollutants/*analysis Chromatography, Gas Environmental Monitoring/*statistics & numerical data Extraction and Processing Industry/*statistics & numerical data Methane/*analysis *Natural Gas United States greenhouse gas emissions hydraulic fracturing

Carbon Capture and Utilization Update - Al-Mamoori, Ahmed; Krishnamurthy, Anirudh; Rownaghi, Ali A.; Rezaei, Fateme (Energy Technology, 2017)

Greater Focus Needed On Methane Leakage From Natural Gas Infrastructure - Alvarez, R. A.; Pacala, S. W.; Winebrake, J. J.; Chameides, W. L.; Hamburg, S. P. (Proceedings of the National Academy of Sciences USA, 2012)

A review of scenario planning - Amer, Muhammad; Daim, Tugrul U.; Jetter, Antonie (Futures, 2013)

Report Card for America's Infrastructure - ASCE (American Society for Civil Engineers, 2013)

Recent decreases in fossil-fuel emissions of ethane and methane derived from firn air - Aydin, M.; Verhulst, K. R.; Saltzman, E. S.; Battle, M. O.; Montzka, S. A.; Blake, D. R.; Tang, Q.; Prather, M. J. (Nature, 2011)
Keywords: Antarctic Regions Atmosphere/*chemistry Biofuels Biomass Ethane/*analysis Fires *Fossil Fuels/history/utilization Geography Greenland History, 20th Century History, 21st Century Ice/analysis Methane/*analysis Models, Theoretical Snow/*chemistry

Ending Energy Subsidies: Environmental No-Brainer, Political No-Winner - Ball, J. (New Republic, 2013)

Assessing the Role of Distributed Power Systems in the U.S. Power Sector - Banks, John P.; Massy, Kevin; Wood, Lisa V.; Carl, Jeremy; Wagner, Amy Guy; Mokrian, Pedram; Simjanovic, Jelena; Slayton, David (The Brookings Institution Energy Security Initiative and The Hoover Institution Shultz-Stephenson Task Force on Energy Policy, 2011)

Field-scale environmental impacts - BANR (Bioenergy Alliance Network of the Rockies, 2017)

Tracking the Sun IX: The Installed Price of Residential and Non-Residential Photovoltaic Systems in the United States. LBNL-1006036 - Barbose, G; Dargouth, N. (Lawrence Berkeley National Laboratory, Berkeley, California., 2016)

Mitigation from a cross-sectoral perspective - Barker, T.; Bashmakov, I.; Alharthi, A.; Amann, M.; L. Cifuentes; Drexhage, J.; Duan, M.; Edenhofer, O.; Flannery, B.; Grubb, M.; Hoogwijk, M.; Ibitoye, F. I.; et al. (Climate Change 2007: Mitigation. Contribution of Working Group III to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change, 2007)

Making the Grade: How Investments in America’s Infrastructure Benefit Our Economy and Environment - Barrett, Jim; McCulloch, Rob; Johnson, Roxanne (BlueGreen Alliance, 2014)

Global, Regional, and National Fossil-Fuel CO2 Emissions - Boden, T.A.; Marland, G.; Andres, R.J. (Carbon Dioxide Information Analysis Center (CDIAC), U. S. Department of Energy, Oak Ridge National Laboratory, 2016)

Scenario types and techniques: Towards a user's guide - Börjeson, Lena; Höjer, Mattias; Dreborg, Karl-Henrik; Ekvall, Tomas; Finnveden, Göran (Futures, 2006)

BP Statistical Review of World Energy June 2016 - BP (BP, 2016)

BP Statistical Review of World Energy, June 2017 - BP (BP, 2017)

BP Energy Outlook 2017 - BP (BP, 2017)

Consequential and attributional approaches to LCA: A guide to policy makers with specific reference to greenhouse gas LCA of biofuels - Brander, M.; Tipper, R.; Hutchison, C.; Davis, G. (Ecometrica Press, 2009)

Methane Leaks From North American Natural Gas Systems - Brandt, A. R.; Heath, G. A.; Kort, E. A.; O'Sullivan, F.; Petron, G.; Jordaan, S. M.; Tans, P.; Wilcox, J.; Gopstein, A. M.; Arent, D.; Wofsy, S.; Brown, N. J.; et al. (Science, 2014)
Keywords: Atmosphere/*chemistry Decision Making *Global Warming Methane/*analysis Natural Gas/*analysis *Policy Making United States

Energy Systems - Bruckner, T.; Bashmakov, I.A.; Mulugetta, Y.; Chum, H.; de la Vega Navarro, A; Edmonds, J.; Faaij, A.; Fungtammasan, B.; Garg, A.; Hertwich, E.; Honnery, D.; Infield, D.; et al. (Mitigation of Climate Change. Contribution of Working Group III to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change, 2014)

Global non-linear effect of temperature on economic production - Burke, Marshall; Hsiang, Solomon M.; Miguel, Edward (Nature, 2015)

Carbon dioxide emissions in the short run: The rate and sources of economic growth matter - Burke, Paul J.; Shahiduzzaman, Md; Stern, David I. (Global Environmental Change, 2015)
Keywords: Economic growth Emissions Pollution Business cycle Asymmetry Sector

Influence of Methane Emissions and Vehicle Efficiency on the Climate Implications of Heavy-Duty Natural Gas Trucks - Camuzeaux, Jonathan R.; Alvarez, Ramón A.; Brooks, Susanne A.; Browne, Joshua B.; Sterner, Thomas (Environmental Science and Technology, 2015)

First State of the Carbon Cycle Report (SOCCR): The North American Carbon Budget and Implications For the Global Carbon Cycle. A Report By the U.S. Climate Change Science Program and the Subcommittee On Global Change Research - CCSP (National Oceanic and Atmospheric Administration, National Climatic Data Center, Asheville, NC, USA, 242 pp., 2007)

Vision 2050, the Future of Canada's Electricity System - CEA (Canadian Electricity Association, 2014)

The Impact of State Level Building Codes on Residential Electricity Consumption. CEC-500-2012-081 - CEC (California Energy Commission, 2014)

Guide to Electric Power in Mexico - CEE; ITAM (Center for Energy Economics (CEE), Bureau of Economic Geology, the University of Texas at Austin and Instituto Tecnológico y de Estudios Superiores de Monterrey, Instituto Tecnológico Autonomo de Mexico (ITAM), 2013)

Benchmarks of Global Clean Energy Manufacturing - CEMAC (Clean Energy Manufacturing Analysis Center, 2017)

CARMA database - CGD (Carbon Monitoring for Action, Center for Global Development, 2016)

Evaluation of a proposal for reliable low-cost grid power with 100% wind, water, and solar - Clack, Christopher T. M.; Qvist, Staffan A.; Apt, Jay; Bazilian, Morgan; Brandt, Adam R.; Caldeira, Ken; Davis, Steven J.; Diakov, Victor; Handschy, Mark A.; Hines, Paul D. H.; Jaramillo, Paulina; Kammen, Daniel M.; et al. (Proceedings of the National Academy of Sciences USA, 2017)
Previous analyses have found that the most feasible route to a low-carbon energy future is one that adopts a diverse portfolio of technologies. In contrast, Jacobson et al. (2015) consider whether the future primary energy sources for the United States could be narrowed to almost exclusively wind, solar, and hydroelectric power and suggest that this can be done at “low-cost” in a way that supplies all power with a probability of loss of load “that exceeds electric-utility-industry standards for reliability”. We find that their analysis involves errors, inappropriate methods, and implausible assumptions. Their study does not provide credible evidence for rejecting the conclusions of previous analyses that point to the benefits of considering a broad portfolio of energy system options. A policy prescription that overpromises on the benefits of relying on a narrower portfolio of technologies options could be counterproductive, seriously impeding the move to a cost effective decarbonized energy system.A number of analyses, meta-analyses, and assessments, including those performed by the Intergovernmental Panel on Climate Change, the National Oceanic and Atmospheric Administration, the National Renewable Energy Laboratory, and the International Energy Agency, have concluded that deployment of a diverse portfolio of clean energy technologies makes a transition to a low-carbon-emission energy system both more feasible and less costly than other pathways. In contrast, Jacobson et al. [Jacobson MZ, Delucchi MA, Cameron MA, Frew BA (2015) Proc Natl Acad Sci USA 112(49):15060–15065] argue that it is feasible to provide “low-cost solutions to the grid reliability problem with 100% penetration of WWS [wind, water and solar power] across all energy sectors in the continental United States between 2050 and 2055”, with only electricity and hydrogen as energy carriers. In this paper, we evaluate that study and find significant shortcomings in the analysis. In particular, we point out that this work used invalid modeling tools, contained modeling errors, and made implausible and inadequately supported assumptions. Policy makers should treat with caution any visions of a rapid, reliable, and low-cost transition to entire energy systems that relies almost exclusively on wind, solar, and hydroelectric power.

Technology and U.S. Emissions Reductions Goals: Results of the EMF 24 Modeling Exercise - Clarke, Leon E.; Fawcett, Allen A.; Weyant, John P.; McFarland, James; Chaturvedi, Vaibhav; Zhou, Yuyu (The Energy Journal, 2014)

Sustainability Policy: Hastening the Transition to a Cleaner Economy - Cohen, Steven; Eimicke, William; Miller, Alison (Wiley, 2015)

Strategic Plan of the Commission for Environmental Cooperation, 2015-2020 - Commission for Environmental Cooperation (2015)

Contribution of air conditioning adoption to future energy use under global warming - Davis, Lucas W.; Gertler, Paul J. (Proceedings of the National Academy of Sciences, 2015)
The use of air conditioning is poised to increase dramatically over the next several decades as global temperatures go up and incomes rise around the world. In this paper, we use high-quality microdata from Mexico to characterize empirically the relationship between temperature, income, and air conditioning. We describe both how electricity consumption increases with temperature given current levels of air conditioning, and how climate and income drive air conditioning adoption decisions. We then combine these estimates with predicted end-of-century temperature changes to forecast future energy consumption. Overall, our results point to air conditioning impacts being considerably larger than previously believed.As household incomes rise around the world and global temperatures go up, the use of air conditioning is poised to increase dramatically. Air conditioning growth is expected to be particularly strong in middle-income countries, but direct empirical evidence is scarce. In this paper we use high-quality microdata from Mexico to describe the relationship between temperature, income, and air conditioning. We describe both how electricity consumption increases with temperature given current levels of air conditioning, and how climate and income drive air conditioning adoption decisions. We then combine these estimates with predicted end-of-century temperature changes to forecast future energy consumption. Under conservative assumptions about household income, our model predicts near-universal saturation of air conditioning in all warm areas within just a few decades. Temperature increases contribute to this surge in adoption, but income growth by itself explains most of the increase. What this will mean for electricity consumption and carbon dioxide emissions depends on the pace of technological change. Continued advances in energy efficiency or the development of new cooling technologies could reduce the energy consumption impacts. Similarly, growth in low-carbon electricity generation could mitigate the increases in carbon dioxide emissions. However, the paper illustrates the enormous potential impacts in this sector, highlighting the importance of future research on adaptation and underscoring the urgent need for global action on climate change.

Energy-Savings States of America: How Every State Benefits From National Appliance Standards - deLaski, Andrew; Mauer, Joanna (Appliance Standards Awareness Project and American Council for Energy-Efficient Economy, 2017)

Providing all global energy with wind, water, and solar power, Part II: Reliability, system and transmission costs, and policies - Delucchi, Mark A.; Jacobson, Mark Z. (Energy Policy, 2011)
Keywords: Wind power Solar power Water power

Budget 2009: Canada's Economic Action Plan - Department of Finance Canada (2009)

National Inventory Report 1990-2014: Greenhouse Gas Sources and Sinks in Canada - ECCC (Environment and Climate Change Canada, 2016)

Canada's Second Biennial Report on Climate Change - ECCC (Environment and Climate Change Canada,, 2016)

Canada's 2016 Greenhouse Gas Emissions Reference Case - ECCC (Sector details for high and low scenarios supplied by direct correspondence with Hilary Paulin, Strategic Policy Branch, Environment and Climate Change Canada, Aug. 18, 2017, 2016)

National Inventory Report 1990-2015: Greenhouse Gas Sources and Sinks in Canada, Canada’s Submission to the United Nations Framework Convention on Climate Change, Part 1 - ECCC (Environment and Climate Change Canada, 2017)

Transforming America’s Power Industry: The Investment Challenge 2010-2030 - Edison Electric Institute (The Edison Foundation, 2008)

U.S. Households Are Incorporating Energy-efficient Features - EIA (Today in Energy, 2011)

Electricity Storage Technologies Can Be Used for Energy Management and Power Quality - EIA (Today in Energy, 2011)

CBECS Energy Usage Summary - EIA (U.S. Energy Information Adminstration,, 2012)

Natural Gas Consumption Reflects Shifting Sectoral Patterns - EIA (Today in Energy, 2012)

Energy Star Homes Accounted for 26% of New Construction in 2011 - EIA (Today in Energy, 2012)

Most States Have Renewable Portfolio Standards - EIA (Today in Energy, 2012)

Heating and Cooling No Longer Majority of U.S. Home Energy Use - EIA (Today in Energy, 2013)

Pumped Storage Provides Grid Reliability Even With Net Generation Loss - EIA (Today in Energy, 2013)

Crude Oil Reserves At Start of 2013 Reach Highest Level Since 1976 - EIA (Today in Energy, 2014)

Oil and Natural Gas Resource Categories Reflect Varying Degrees of Certainty - EIA (Today in Energy, 2014)

Mexico, International Energy Data and Analysis - EIA (U.S. Energy Information Administration, 2015)

Annual Energy Outlook 2015 With Projections to 2040 Report. DOE/EIA-0383(2015) - EIA (U.S. Energy Information Administration, 2015)

U.S. energy intensity projected to continue its steady decline through 2040 - EIA (Today in Energy, 2015)

International Data - EIA (U.S. Energy Information Adminstration, 2016)

U.S. Crude Oil and Natural Gas Proved Reserves, Year-End 2015 Report - EIA (U.S. Energy Information Adminstration, 2016)

Annual Energy Outlook 2016 - EIA (U.S. Energy Information Adminstration, 2016)

Petroleum and Other Liquids - EIA (U.S. Energy Information Adminstration, 2016)

Most Natural Gas Production Growth is Expected to Come From Shale Gas and Tight Oil Plays - EIA (Today in Energy, 2016)

Natural Gas - EIA (U.S. Energy Information Adminstration, 2016)

Electricity - EIA (U.S. Energy Information Adminstration, 2016)

Electric Power Annual, 2014 Report - EIA (U.S. Energy Information Adminstration, 2016)

Wind Generation Share Exceeded 10% in 11 States in 2015 - EIA (Today in Energy, 2016)

How Much Natural Gas Does the United States Have, and How Long Will It Last? FAQs - EIA (U.S. Energy Information Administration, 2017)

U.S. Households’ Heating Equipment Choices Are Diverse and Vary By Climate Region - EIA (Today in Energy, 2017)

Use of energy in the United States explained, energy use for transportation - EIA (U.S. Energy Information Administration, 2017)

How Much Shale (tight) Oil is Produced in the United States? FAQs - EIA (U.S. Energy Information Administration, 2017)

Natural Gas-fired Power Plants Lead Electric Capacity Additions in Mexico - EIA (Today in Energy, 2017)

What is U.S. Electricity Generation By Energy Source? FAQs - EIA (U.S. Energy Information Administration, 2017)

Steel Industry Analysis Brief - EIA (U.S. Energy Information Administration, 2017)

Carbon Intensity of Energy Use is Lowest in U.S. Industrial and Electric Power Sectors - EIA (Today in Energy, 2017)

Annual Energy Outlook 2017 With Projections to 2050 - EIA (U.S. Energy Information Adminstration, 2017)

Natural Gas Gross Withdrawals - EIA (U.S. Energy Information Administration, 2017)

Estimating U.S. Government Subsidies to Energy Sources: 2002-2008 - Environmental Law Institute (2009)

The Electric Vehicle World Sales Database - EV-Volumes (2017)

The Outlook for Energy, a View to 2040 - ExxonMobil (2017)

U.S. Energy Policy in the Trump Administration and 115th Congress - EY (Ernst & Young Global Limited, 2017)

Ethanol can contribute to energy and environmental goals - Farrell, A. E.; Plevin, R. J.; Turner, B. T.; Jones, A. D.; O'Hare, M.; Kammen, D. M. (Science, 2006)
Keywords: *Biotechnology *Cellulose/metabolism *Energy-Generating Resources Environment *Ethanol/metabolism Greenhouse Effect *Zea mays/metabolism

Overview of EMF 24 Policy Scenarios - Fawcett, Allen A.; Clarke, Leon C.; Rausch, Sebastian; Weyant, John P. (The Energy Journal, 2014)

Introduction to EMF 24 - Fawcett, Allen A.; Clarke, Leon E.; Weyant, John P. (The Energy Journal, 2014)

Canada Adopts America's New Fuel Economy Standard, for Now - Feldman, Stacy (Inside Climate News, 2009)

Drivers of the U.S. CO2 Emissions 1997-2013 - Feng, K.; Davis, S. J.; Sun, L.; Hubacek, K. (Nature Communicatons, 2015)

Correspondence: Reply to 'Reassessing the Contribution of Natural Gas to U.S. CO2 Emission Reductions Since 2007' - Feng, K.; Davis, S. J.; Sun, L.; Hubacek, K. (Nature Communicatons, 2016)

Ecosystem model parameterization and adaptation for sustainable cellulosic biofuel landscape design - Field, John L.; Marx, Ernie; Easter, Mark; Adler, Paul R.; Paustian, Keith (GCB Bioenergy, 2016)
Keywords: biogeochemistry carbon sequestration cellulosic biofuel ecosystem model parameterization ecosystem modeling feedstock greenhouse gas emissions landscape design marginal land nitrous oxide

Airborne Methane Remote Measurements Reveal Heavy-tail Flux Distribution in Four Corners Region - Frankenberg, C.; Thorpe, A. K.; Thompson, D. R.; Hulley, G.; Kort, E. A.; Vance, N.; Borchardt, J.; Krings, T.; Gerilowski, K.; Sweeney, C.; Conley, S.; Bue, B. D.; et al. (Proceedings of the National Academy of Sciences USA, 2016)
Keywords: Four Corners heavy-tail methane remote sensing

Switch: A Planning Tool for Power Systems With Large Shares of Intermittent Renewable Energy - Fripp, M. (Environmental Science and Technology, 2012)
Keywords: California Carbon Dioxide/analysis Coal/economics Conservation of Natural Resources/economics Costs and Cost Analysis Electricity *Models, Economic Natural Gas/economics Power Plants/*economics Renewable Energy/*economics Solar Energy/economics Vehicle Emissions/analysis Wind

The technical, geographical, and economic feasibility for solar energy to supply the energy needs of the US - Fthenakis, Vasilis; Mason, James E.; Zweibel, Ken (Energy Policy, 2009)
Keywords: Solar Global climate Photovoltaics

Betting On Negative Emissions - Fuss, Sabine; Canadell, Josep G.; Peters, Glen P.; Tavoni, Massimo; Andrew, Robbie M.; Ciais, Philippe; Jackson, Robert B.; Jones, Chris D.; Kraxner, Florian; Nakicenovic, Nebosja; Le Quéré, Corinne; Raupach, Michael R.; et al. (Nature Climate Change, 2014)

Sustainability guidelines and forest market response: An assessment of European Union pellet demand in the southeastern United States - Galik, Christopher S.; Abt, Robert C. (GCB Bioenergy, 2016)

The Age of Public Infrastructure in Canada - Gaudreault, Valerie; Lemire, Patrick (Statistics Canada, 2009)

The Global Status of CCS: 2016. Summary Report - Global CCS Institute (2016)

Rise in U.S. Gas Production Fuels Unexpected Plunge in Emissions - Gold, Russell (The Wall Street Journal, 2013)

Alberta Energy: Facts and Statistics - Government of Alberta [Canada] (2016)

Responses of Energy Use to Climate Change: A Climate Modeling Study - Hadley, Stanton W.; Erickson, David J.; Hernandez, Jose Luis; Broniak, Christine T.; Blasing, T. J. (Geophysical Research Letters, 2006)

Transmission and Distribution Infrastructure - Harris Williams & Co. (Harris Williams and Co., 2014)

Carbon Capture and Storage: How Green Can Black Be? - Haszeldine, R. S. (Science, 2009)

Demographic Trends in the 20th Century - Hobbs, Frank; Stoops, Nicole (U.S. Census Bureau, Census 2000 Special Reports, Series CENSR-4, 2002)

Estimating the Cost of Saving Electricity Through U.S. Utility Customer-funded Energy Efficiency Programs - Hoffman, Ian M.; Goldman, Charles A.; Rybka, Gregory; Leventis, Greg; Schwartz, Lisa; Sanstad, Alan H.; Schiller, Steven (Energy Policy, 2017)

Determinism and backcasting in future studies - Höjer, Mattias; Mattsson, Lars-Göran (Futures, 2000)

Can Coal Make a Comeback? - Houser, Trevor; Bordoff, Jason; Marsters, Peter (Columbia University, School for International and Public Affairs, Center on Global Energy Policy, 2017)

Methane and the Greenhouse-gas Footprint of Natural Gas From Shale Formations - Howarth, Robert W.; Santoro, Renee; Ingraffea, Anthony (Climatic Change, 2011)

The Variation of Climate Change Impact on Building Energy Consumption to Building Type and Spatiotemporal Scale - Huang, Jianhua; Gurney, Kevin Robert (Energy, 2016)

Evidence for Intensification of the Global Water Cycle: Review and Synthesis - Huntington, Thomas G. (Journal of Hydrology, 2006)

Mexico - ICAP (International Carbon Action Partnership, 2016)

Mexico Light-duty Vehicle CO2 and Fuel Economy Standards: Policy Update - ICCT (International Council on Clean Transportation, 2013)

Energy Policies of IEA Countries - Canada 2009 Review - IEA (International Energy Agency, 2010)

Resources to Reserves 2013, Oil, Gas and Coal Technologies for the Energy Markets of the Future - IEA (International Energy Agency, 2013)

Energy Efficiency Market Report - IEA (International Energy Agency, 2015)

World Energy Outlook 2015 - IEA (International Energy Agency, 2015)

IEA Fossil Fuel Subsidy Database - IEA (International Energy Agency, 2015)

Energy Statistics: Energy Balances, Projections for IEA Countries - IEA (International Energy Agency, 2016)

World Energy Statistics 2016 Edition Database Documentation - IEA (International Energy Agency, 2016)

World CO2 Emissions From Fuel Combustion Database - IEA (International Energy Agency, 2016)

Mexico Energy Outlook: World Energy Outlook Special Report - IEA (International Energy Agency, 2016)

The Scope of Fossil-Fuel Subsidies in 2009 and a Roadmap for Phasing Out Fossil-fuel Subsidies - IEA; OECD; World Bank (International Energy Agency, OECD, World Bank, 2010)

Joint Report By IEA, OPEC, OECD and World Bank on Fossil-fuel and Other Energy Subsidies: An Update of the G20 Pittsburgh and Toronto Commitments - IEA; OPEC; OECD; World Bank (2011)

North American Midstream Infrastructure Through 2035: Leaning into the Headwinds Report 2016.02 - INGAA (INGAA Foundation, 2016)

Providing all global energy with wind, water, and solar power, Part I: Technologies, energy resources, quantities and areas of infrastructure, and materials - Jacobson, Mark Z.; Delucchi, Mark A. (Energy Policy, 2011)
Keywords: Wind power Solar power Water power

100% clean and renewable wind, water, and sunlight (WWS) all-sector energy roadmaps for the 50 United States - Jacobson, Mark Z.; Delucchi, Mark A.; Bazouin, Guillaume; Bauer, Zack A. F.; Heavey, Christa C.; Fisher, Emma; Morris, Sean B.; Piekutowski, Diniana J. Y.; Vencill, Taylor A.; Yeskoo, Tim W. (Energy and Environmental Science, 2015)
This study presents roadmaps for each of the 50 United States to convert their all-purpose energy systems (for electricity, transportation, heating/cooling, and industry) to ones powered entirely by wind, water, and sunlight (WWS). The plans contemplate 80-85% of existing energy replaced by 2030 and 100% replaced by 2050. Conversion would reduce each state's end-use power demand by a mean of [similar]39.3% with [similar]82.4% of this due to the efficiency of electrification and the rest due to end-use energy efficiency improvements. Year 2050 end-use U.S. all-purpose load would be met with [similar]30.9% onshore wind, [similar]19.1% offshore wind, [similar]30.7% utility-scale photovoltaics (PV), [similar]7.2% rooftop PV, [similar]7.3% concentrated solar power (CSP) with storage, [similar]1.25% geothermal power, [similar]0.37% wave power, [similar]0.14% tidal power, and [similar]3.01% hydroelectric power. Based on a parallel grid integration study, an additional 4.4% and 7.2% of power beyond that needed for annual loads would be supplied by CSP with storage and solar thermal for heat, respectively, for peaking and grid stability. Over all 50 states, converting would provide [similar]3.9 million 40-year construction jobs and [similar]2.0 million 40-year operation jobs for the energy facilities alone, the sum of which would outweigh the [similar]3.9 million jobs lost in the conventional energy sector. Converting would also eliminate [similar]62 000 (19 000-115 000) U.S. air pollution premature mortalities per year today and [similar]46 000 (12 000-104 000) in 2050, avoiding [similar]$600 ($85-$2400) bil. per year (2013 dollars) in 2050, equivalent to [similar]3.6 (0.5-14.3) percent of the 2014 U.S. gross domestic product. Converting would further eliminate [similar]$3.3 (1.9-7.1) tril. per year in 2050 global warming costs to the world due to U.S. emissions. These plans will result in each person in the U.S. in 2050 saving [similar]$260 (190-320) per year in energy costs ($2013 dollars) and U.S. health and global climate costs per person decreasing by [similar]$1500 (210-6000) per year and [similar]$8300 (4700-17 600) per year, respectively. The new footprint over land required will be [similar]0.42% of U.S. land. The spacing area between wind turbines, which can be used for multiple purposes, will be [similar]1.6% of U.S. land. Thus, 100% conversions are technically and economically feasible with little downside. These roadmaps may therefore reduce social and political barriers to implementing clean-energy policies.

Book Review: The essence of scenarios: learning from the shell experience, Amsterdam University Press. - Jefferson, Michael (Technological Forecasting and Social Change, 2015)

Methane Emissions Estimate From Airborne Measurements Over a Western United States Natural Gas Field - Karion, A.; Sweeney, C.; Petron, G.; Frost, G.; Hardesty, R.M.; Kofler, J.; Miller, Ben R.; Newberger, T.; Wolter, S.; Banta, R.; Brewer, A.; Dlugokencky, E.; et al. (Geophysical Research Letters, 2013)

U.S. Reshoring: Over Before It Began? - Kearney, A.T. (AT Kearney, Inc., 2015)

SAB Review of EPA's Accounting Framework for Biogenic CO2 Emissions From Stationary Sources - Khanna, M.; Abt, R.; Barlaz, M.; Birdsey, R.; Buford, M.; Harmon, M.; Hill, J.; Kelley, S.; Nelson, R.; Olander, L.; Reilly, J.; Rice, C.; et al. (U.S. EPA Science Advisory Board Biogenic Carbon Emissions Panel, 2012)

Despite Fears, Mexico's Manufacturing Boom is Lifting U.S. Workers - Kitroeff, N. (Los Angeles Times, 2016)

Energy Storage Deployment and Innovation for the Clean Energy Transition - Kittner, Noah; Lill, Felix; Kammen, Daniel M. (Nature Energy, 2017)

Emissions of CH4 and N2O Over the United States and Canada Based On a Receptor-oriented Modeling Framework and COBRA-NA Atmospheric Observations - Kort, Eric A.; Eluszkiewicz, Janusz; Stephens, Britton B.; Miller, John B.; Gerbig, Christoph; Nehrkorn, Thomas; Daube, Bruce C.; Kaplan, Jed O.; Houweling, Sander; Wofsy, Steven C. (Geophysical Research Letters, 2008)

Reassessing the Contribution of Natural Gas to U.S. CO2 Emission Reductions Since 2007 - Kotchen, Matthew J.; Mansur, Erin T. (Nature Communications, 2016)

Pathways limiting warming to 1.5 degrees C: A tale of turning around in no time? - Kriegler, E.; Luderer, G.; Bauer, N.; Baumstark, L.; Fujimori, S.; Popp, A.; Rogelj, J.; Strefler, J.; van Vuuren, D. P. (Philosophical Transactions of the Royal Society A: Mathematical, Physical and Engineering Sciences, 2018)
We explore the feasibility of limiting global warming to 1.5 degrees C without overshoot and without the deployment of carbon dioxide removal (CDR) technologies. For this purpose, we perform a sensitivity analysis of four generic emissions reduction measures to identify a lower bound on future CO2 emissions from fossil fuel combustion and industrial processes. Final energy demand reductions and electrification of energy end uses as well as decarbonization of electricity and non-electric energy supply are all considered. We find the lower bound of cumulative fossil fuel and industry CO2 emissions to be 570 GtCO2 for the period 2016-2100, around 250 GtCO2 lower than the lower end of available 1.5 degrees C mitigation pathways generated with integrated assessment models. Estimates of 1.5 degrees C-consistent CO2 budgets are highly uncertain and range between 100 and 900 GtCO2 from 2016 onwards. Based on our sensitivity analysis, limiting warming to 1.5 degrees C will require CDR or terrestrial net carbon uptake if 1.5 degrees C-consistent budgets are smaller than 650 GtCO2 The earlier CDR is deployed, the more it neutralizes post-2020 emissions rather than producing net negative emissions. Nevertheless, if the 1.5 degrees C budget is smaller than 550 GtCO2, temporary overshoot of the 1.5 degrees C limit becomes unavoidable if CDR cannot be ramped up faster than to 4 GtCO2 in 2040 and 10 GtCO2 in 2050.This article is part of the theme issue 'The Paris Agreement: understanding the physical and social challenges for a warming world of 1.5 degrees C above pre-industrial levels'.
Kriegler, Elmar Luderer, Gunnar Bauer, Nico Baumstark, Lavinia Fujimori, Shinichiro Popp, Alexander Rogelj, Joeri Strefler, Jessica van Vuuren, Detlef P eng England 2018/04/04 06:00 Philos Trans A Math Phys Eng Sci. 2018 May 13;376(2119). pii: rsta.2016.0457. doi: 10.1098/rsta.2016.0457.
Keywords: 1.5 degrees C goal CO-2 emissions carbon budget carbon dioxide removal integrated assessment mitigation pathways

Direct Measurements Show Decreasing Methane Emissions From Natural Gas Local Distribution Systems in the United States - Lamb, Brian K.; Edburg, Steven L.; Ferrara, Thomas W.; Howard, Touché; Harrison, Matthew R.; Kolb, Charles E.; Townsend-Small, Amy; Dyck, Wesley; Possolo, Antonio; Whetstone, James R. (Environmental Science and Technology, 2015)

What Drives Land-Use Change in the United States? A National Analysis of Landowner Decisions - Lubowski, R. N.; Plantinga, A. J.; Stavins, R. N. (Land Economics, 2008)

Future cost-competitive electricity systems and their impact on US CO2 emissions - MacDonald, Alexander E.; Clack, Christopher T. M.; Alexander, Anneliese; Dunbar, Adam; Wilczak, James; Xie, Yuanfu (Nature Climate Change, 2016)

Methane Emissions From United States Natural Gas Gathering and Processing - Marchese, A. J.; Vaughn, T. L.; Zimmerle, D. J.; Martinez, D. M.; Williams, L. L.; Robinson, A. L.; Mitchell, A. L.; Subramanian, R.; Tkacik, D. S.; Roscioli, J. R.; Herndon, S. C. (Environmental Science and Technology, 2015)
Keywords: Air Pollutants/*analysis Computer Simulation Greenhouse Effect Methane/*analysis Models, Theoretical Monte Carlo Method Natural Gas/*analysis *Oil and Gas Fields United States

Urbanization and the carbon cycle: Contributions from social science - Marcotullio, P. J.; Hughes, S.; Sarzynski, A.; Pincetl, S.; Pena, L. S.; Romero-Lankao, P.; Runfola, D.; Seto, K. C. (Earths Future, 2014)
This paper outlines the contributions of social science to the study of interactions between urbanization patterns and processes and the carbon cycle, and identifies gaps in knowledge and priority areas for future social scientific research contributions. While previously studied as a unidimensional process, we conceptualize urbanization as a multidimensional, social and biophysical process driven by continuous changes across space and time in various subsystems including biophysical, built environment, and socio-institutional (e.g., economic, political, demographic, behavioral, and sociological). We review research trends and findings focused on the socio-institutional subsystem of the urbanization process, and particularly the dynamics, relationships, and predictions relevant to energy use and greenhouse gas emissions. Our findings suggest that a multidimensional perspective of urbanization facilitates a wider spectrum of research relevant to carbon cycle dynamics, even within the socio-institutional subsystem. However, there is little consensus around the details and mechanisms underlying the relationship between urban socio-institutional subsystems and the carbon cycle. We argue that progress in understanding the relationship between urbanization and the carbon cycle may be achieved if social scientists work collaboratively with each other as well as with scientists from other disciplines. From this review, we identify research priorities where collaborative social scientific efforts are necessary in conjunction with other disciplinary approaches to generate a more complete understanding of urbanization as a process and its relationship to the carbon cycle.
Cn0wy Times Cited:18 Cited References Count:199
Keywords: greenhouse-gas emissions household energy-requirements climate-change united-states electricity consumption developing-countries CO2 emissions sustainable consumption environmental-impact economic-development

Tesla’s Model 3 is Making Electric Vehicles Successful Even Before Its Launch - Marshall, Aarian (Wired Transportation, 2017)

Urban Growth, Climate Change, and Freshwater Availability - McDonald, R. I.; Green, P.; Balk, D.; Fekete, B. M.; Revenga, C.; Todd, M.; Montgomery, M. (Proceedings of the National Academy of Sciences USA, 2011)
Keywords: *Climate Change *Fresh Water Humans *Population Growth *Urban Population *Urbanization

Mexico’s First Power Auction Awards 1,720 Megawatts of Wind & Solar - Meyers, Glenn (Clean Technica, 2016)

SunShot Solar Power Reduces Costs and Uncertainty in Future Low-carbon Electricity Systems - Mileva, A.; Nelson, J. H.; Johnston, J.; Kammen, D. M. (Environmental Science and Technology, 2013)
Keywords: *Electricity Solar Energy/*economics Uncertainty United States

Emission budgets and pathways consistent with limiting warming to 1.5 °C - Millar, Richard J.; Fuglestvedt, Jan S.; Friedlingstein, Pierre; Rogelj, Joeri; Grubb, Michael J.; Matthews, H. Damon; Skeie, Ragnhild B.; Forster, Piers M.; Frame, David J.; Allen, Myles R. (Nature Geoscience, 2017)

Anthropogenic Emissions of Methane in the United States - Miller, S. M.; Wofsy, S. C.; Michalak, A. M.; Kort, E. A.; Andrews, A. E.; Biraud, S. C.; Dlugokencky, E. J.; Eluszkiewicz, J.; Fischer, M. L.; Janssens-Maenhout, G.; Miller, B. R.; Miller, J. B.; et al. (Proceedings of the National Academy of Sciences USA, 2013)

The Legacy of Uranium Development on or Near Indian Reservations and Health Implications Rekindling Public Awareness - Moore-Nall, Anita (Geosciences, 2015)

Anthropogenic and Natural Radiative Forcing - Myhre, G.; Shindell, D.; Bréon, F.-M.; Collins, W.; Fuglestvedt, J.; Huang, J.; Koch, D.; Lamarque, J.-F.; Lee, D.; Mendoza, B.; Nakajima, T.; Robock, A.; et al. (Climate Change 2013: The Physical Science Basis. Contribution of Working Group I to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change, 2013)

Socioeconomic driving forces of emissions scenarios - Nakicenovic, N. (The Global Carbon Cycle: Integrating Humans, Climate and the Natural World, 2004)

Canada's Energy Future 2016, Energy Supply and Demand Projections to 2040 - National Energy Board (National Energy Board Canada, 2016)

Comprehensive Energy Use Database, Tables 20 and 24 - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2015)

Energy Fact Book, 2015-2016 - Natural Resources Canada (Natural Resources Canada, 2016)

About Renewable Energy - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2016)

Energy Efficiency Trends in Canada, 1990-2013 Report - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2016)

Transportation Sector - Natural Resources Canada (Energy Use Data Handbook, 2016)

High-resolution Modeling of the Western North American Power System Demonstrates Low-cost and Low-carbon Futures - Nelson, James; Johnston, Josiah; Mileva, Ana; Fripp, Matthias; Hoffman, Ian; Petros-Good, Autumn; Blanco, Christian; Kammen, Daniel M. (Energy Policy, 2012)

Carbon Dioxide Capture and Storage, RD&D Roadmap - NETL (U.S. Department of Energy, National Energy Technology Laboratory, 2010)

Carbon Dioxide Enhanced Oil Recovery, Untapped Domestic Energy Supply and Long Term Carbon Storage Solution - NETL (U.S. Department of Energy, National Energy Technology Laboratory, 2017)

World Nuclear Generation and Capacity - Nuclear Energy Institute (2017)

Unmask temporal trade-offs in climate policy debates - Ocko, I. B.; Hamburg, S. P.; Jacob, D. J.; Keith, D. W.; Keohane, N. O.; Oppenheimer, M.; Roy-Mayhew, J. D.; Schrag, D. P.; Pacala, S. W. (Science, 2017)

Environmental Performance Review, Mexico 2013 - OECD (Organisation for Economic Co-operation and Development, 2013)

The North American Carbon Budget Past and Present - Pacala, S.; R.A. Birdsey; S.D. Bridgham; R.T. Conant; K. Davis; B. Hales; R.A. Houghton; J.C. Jenkins; M. Johnston; G. Marland; K. Paustian (First State of the Carbon Cycle Report (SOCCR): The North American Carbon Budget and Implications For the Global Carbon Cycle. A Report By the U.S. Climate Change Science Program and the Subcommittee on Global Change Research, 2007)

Quantifying atmospheric methane emissions from oil and natural gas production in the Bakken shale region of North Dakota - Peischl, J.; Karion, A.; Sweeney, C.; Kort, E. A.; Smith, M. L.; Brandt, A. R.; Yeskoo, T.; Aikin, K. C.; Conley, S. A.; Gvakharia, A.; Trainer, M.; Wolter, S.; et al. (Journal of Geophysical Research: Atmospheres, 2016)

Quantifying Atmospheric Methane Emissions From the Haynesville, Fayetteville, and Northeastern Marcellus Shale Gas Production Regions - Peischl, J.; Ryerson, T. B.; Aikin, K. C.; de Gouw, J. A.; Gilman, J. B.; Holloway, J. S.; Lerner, B. M.; Nadkarni, R.; Neuman, J. A.; Nowak, J. B.; Trainer, M.; Warneke, C.; et al. (Journal of Geophysical Research: Atmospheres, 2015)

Scenario Planning: A Tool for Conservation in an Uncertain World - Peterson, Garry D.; Cumming, Graeme S.; Carpenter, Stephen R. (Conservation Biology, 2003)
Abstract: Conservation decisions about how, when, and where to act are typically based on our expectations for the future. When the world is highly unpredictable and we are working from a limited range of expectations, however, our expectations will frequently be proved wrong. Scenario planning offers a framework for developing more resilient conservation policies when faced with uncontrollable, irreducible uncertainty. A scenario in this context is an account of a plausible future. Scenario planning consists of using a few contrasting scenarios to explore the uncertainty surrounding the future consequences of a decision. Ideally, scenarios should be constructed by a diverse group of people for a single, stated purpose. Scenario planning can incorporate a variety of quantitative and qualitative information in the decision?making process. Often, consideration of this diverse information in a systemic way leads to better decisions. Furthermore, the participation of a diverse group of people in a systemic process of collecting, discussing, and analyzing scenarios builds shared understanding. The robustness provided by the consideration of multiple possible futures has served several groups well; we present examples from business, government, and conservation planning that illustrate the value of scenario planning. For conservation, major benefits of using scenario planning are (?1?) increased understanding of key uncertainties, (?2?) incorporation of alternative perspectives into conservation planning, and (?3?) greater resilience of decisions to surprise.

A New Look At Methane and Nonmethane Hydrocarbon Emissions From Oil and Natural Gas Operations in the Colorado Denver-Julesburg Basin - Pétron, Gabrielle; Karion, Anna; Sweeney, Colm; Miller, Benjamin R.; Montzka, Stephen A.; Frost, Gregory J.; Trainer, Michael; Tans, Pieter; Andrews, Arlyn; Kofler, Jonathan; Helmig, Detlev; Guenther, Douglas; et al. (Journal of Geophysical Research: Atmospheres, 2014)

Using Attributional Life Cycle Assessment to Estimate Climate-Change Mitigation Benefits Misleads Policy Makers - Plevin, Richard J.; Delucchi, Mark A.; Creutzig, Felix (Journal of Industrial Ecology, 2014)
Keywords: climate change greenhouse gas (GHG) emissions industrial ecology life cycle assessment (LCA) policy analysis uncertainty

National Infrastructure Program 2014-2018: Analysis and Opportunities - PricewaterhouseCoopers Mexico (PricewaterhouseCoopers, 2014)

More Car Manufaturing Jobs Move South -- to Mexico - Priddle, A.; Snavely, B. (Detroit Free Press, 2015)

The impact and spin-off of participatory backcasting: From vision to niche - Quist, Jaco; Thissen, Wil; Vergragt, Philip J. (Technological Forecasting and Social Change, 2011)
Keywords: Participatory backcasting Stakeholders Learning Future vision System innovation Socio-technical transitions Sustainability foresight

The biogeochemistry of bioenergy landscapes: Carbon, nitrogen, and water considerations - Robertson, G. Philip; Hamilton, Stephen K.; Del Grosso, Stephen J.; Parton, William J. (Ecological Applications, 2011)
Keywords: bioenergy biofuels cellulosic biomass climate mitigation climate stabilization ecosystem modeling global warming potential greenhouse gases nitrogen nitrous oxide soil carbon water quality

Energy backcasting: A proposed method of policy analysis - Robinson, John Bridger (Energy Policy, 1982)
Keywords: Energy Policy analysis Soft energy paths

Unlearning and backcasting: Rethinking some of the questions we ask about the future - Robinson, John B. (Technological Forecasting and Social Change, 1988)

Futures under glass: A recipe for people who hate to predict - Robinson, John B. (Futures, 1990)

Tracking the Progress of Mexico’s Power Sector Reform - Robles, Alejandro Chanona (Woodrow Wilson Center, Mexico Institute, 2016)

Energy system transformations for limiting end-of-century warming to below 1.5 °C - Rogelj, Joeri; Luderer, Gunnar; Pietzcker, Robert C.; Kriegler, Elmar; Schaeffer, Michiel; Krey, Volker; Riahi, Keywan (Nature Climate Change, 2015)

Scenarios towards limiting global mean temperature increase below 1.5 °C - Rogelj, Joeri; Popp, Alexander; Calvin, Katherine V.; Luderer, Gunnar; Emmerling, Johannes; Gernaat, David; Fujimori, Shinichiro; Strefler, Jessica; Hasegawa, Tomoko; Marangoni, Giacomo; Krey, Volker; Kriegler, Elmar; et al. (Nature Climate Change, 2018)
The 2015 Paris Agreement calls for countries to pursue efforts to limit global-mean temperature rise to 1.5 °C. The transition pathways that can meet such a target have not, however, been extensively explored. Here we describe scenarios that limit end-of-century radiative forcing to 1.9 W m−2, and consequently restrict median warming in the year 2100 to below 1.5 °C. We use six integrated assessment models and a simple climate model, under different socio-economic, technological and resource assumptions from five Shared Socio-economic Pathways (SSPs). Some, but not all, SSPs are amenable to pathways to 1.5 °C. Successful 1.9 W m−2 scenarios are characterized by a rapid shift away from traditional fossil-fuel use towards large-scale low-carbon energy supplies, reduced energy use, and carbon-dioxide removal. However, 1.9 W m−2 scenarios could not be achieved in several models under SSPs with strong inequalities, high baseline fossil-fuel use, or scattered short-term climate policy. Further research can help policy-makers to understand the real-world implications of these scenarios.

A Critical Knowledge Pathway to Low-carbon, Sustainable Futures: Integrated Understanding of Urbanization, Urban Areas, and Carbon - Romero-Lankao, Patricia; Gurney, Kevin R.; Seto, Karen C.; Chester, Mikhail; Duren, Riley M.; Hughes, Sara; Hutyra, Lucy R.; Marcotullio, Peter; Baker, Lawrence; Grimm, Nancy B.; Kennedy, Christopher; Larson, Elisabeth; et al. (Earth's Future, 2014)

Remote Sensing of Fugitive Methane Emissions From Oil and Gas Production in North American Tight Geologic Formations - Schneising, Oliver; Burrows, John P.; Dickerson, Russell R.; Buchwitz, Michael; Reuter, Maximilian; Bovensmann, Heinrich (Earth's Future, 2014)
Keywords: greenhouse gas fugitive emissions oil and gas production hydraulic fracturing 1616 Climate variability 1610 Atmosphere 3360 Remote sensing 6324 Legislation and regulations 6615 Legislation and regulations

When and how to use scenario planning: A heuristic approach with illustration - Schoemaker, Paul J. H. (Journal of Forecasting, 1991)
Abstract This paper offers a step?by?step analysis of a heuristic approach to scenario planning, taking a managerial perspective. The scenario method is contrasted in general with more traditional planning techniques, which tend to perform less well when faced with high uncertainty and complexity. An actual case involving a manufacturing company is used to illustrate the main steps of the proposed heuristic. Its essence is to identify relevant trends and uncertainties, and blend them into scenarios that are internally consistent. In addition, the scenarios should bound the range of plausible uncertainties and challenge managerial thinking. Links to decision making are examined next, including administrative policies as well as integrative techniques. At the strategic level, a key?success?factor matrix is proposed for integrating scenarios, competitor analysis and strategic vision. At the operational level, Monte Carlo simulation is suggested and illustrated as one useful technique for combining scenario thinking with formal project evaluation (after appropriate translations). The paper concludes with a general discussion of scenario planning, to place it in a broader perspective.
Keywords: Scenarios Uncertainty Heuristics Managerial decision making

The Global Competitiveness Report 2012-2013 - Schwab, Klaus; Sala-i-Martin, Xavier (World Economic Forum, 2012)

Improved Mechanistic Understanding of Natural Gas Methane Emissions from Spatially Resolved Aircraft Measurements - Schwietzke, S.; Petron, G.; Conley, S.; Pickering, C.; Mielke-Maday, I.; Dlugokencky, E. J.; Tans, P. P.; Vaughn, T.; Bell, C.; Zimmerle, D.; Wolter, S.; King, C. W.; et al. (Environmental Science and Technology, 2017)

Upward Revision of Global Fossil Fuel Methane Emissions Based On Isotope Database - Schwietzke, S.; Sherwood, O. A.; Bruhwiler, L. M.; Miller, J. B.; Etiope, G.; Dlugokencky, E. J.; Michel, S. E.; Arling, V. A.; Vaughn, B. H.; White, J. W.; Tans, P. P. (Nature, 2016)
Keywords: Atmosphere/*chemistry Carbon Isotopes/analysis Coal *Databases, Factual *Fossil Fuels Methane/*analysis Monte Carlo Method Natural Gas Petroleum

Energy Efficiency Resource Standards: A Progress Report on State Experience - Sciortino, M.; Nowak, S.; York, D.; Kushler, M. (American Council for an Energy Efficient Economy, 2011)

Use of U.S. Croplands for Biofuels Increases Greenhouse Gases Through Emissions From Land-use Change - Searchinger, T.; Heimlich, R.; Houghton, R. A.; Dong, F.; Elobeid, A.; Fabiosa, J.; Tokgoz, S.; Hayes, D.; Yu, T. H. (Science, 2008)
Keywords: *Carbon Dioxide/analysis/metabolism *Crops, Agricultural/economics/growth & development Ecosystem *Energy-Generating Resources Environment *Ethanol/metabolism Greenhouse Effect Time Factors Trees United States *Zea mays/growth & development/metabolism

Systema de Informacion Energetica de Mexico - Secretaría de Energía de México (2016)

U.S. Solar Market Insight Report: 2014 Year in Review - SEIA (Greentech Media, Inc. and Solar Energy Industries Association, 2014)

Mexico’s Climate Change Mid-Century Strategy - SEMARNAT-INECC (Ministry of Environment and Natural Resources (SEMARNAT) and National Institute of Ecology and Climate Change (INECC), 2016)

Prospectiva Del Sector Eléctrico, 2015-2029 - SENER (Secretaría de Energía, 2015)

Changes in CO2 emissions over business cycle recessions and expansions in the United States: A decomposition analysis - Shahiduzzaman, M.; Layton, A. (Applied Energy, 2015)
This paper examines the asymmetry of changes in CO2 emissions over business cycle recessions and expansions using yearly data from 1949 and monthly data from 1973 for the United States (US). In addition, decomposition analysis is applied to investigate the relative roles of various proximate contributing factors to observed changes in total and per capita CO2 emissions and emissions intensity, over business cycle phases. The results suggest, inter alia, that aggregate emissions and emissions intensity reduce much faster in contractions than they increase in expansions. In addition, unlike the three previous expansions, in the most recent post-GFC US expansion, emissions per capita have continued to decline, and at a rate very similar to the rate of reduction in preceding contractions. This suggests the real possibility that the most recent contraction may have had an ongoing impact on the path of per capita emissions well beyond the immediate impact experienced during the contraction itself. (C) 2015 Elsevier Ltd. All rights reserved.
Ck3nj Times Cited:20 Cited References Count:63
Keywords: CO2 emissions business cycle decomposition analysis carbon-dioxide emissions interfuel substitution economic-growth environmental-policy empirical-evidence technical change driving forces kuznets curve energy population

Decomposition analysis for assessing the United States 2025 emissions target: How big is the challenge? - Shahiduzzaman, Md; Layton, Allan (Renewable and Sustainable Energy Reviews, 2017)
Keywords: Emissions target USA Decomposition analysis

Approaching Scenario-Based Studies: Three Perceptions about the Future and Considerations for Landscape Planning - Shearer, Allan W (Environment and Planning B: Planning and Design, 2005)
Scenario-based investigations of possible futures have been used since the middle of the 20th century to help decisionmakers cope with alternative courses of action and elements of uncertainty. Since the early 1970s, they have been increasingly used for landscape planning. Each scenario-based study is founded on assumptions of possible change. Often these beliefs are only implicit among scenario creators and scenario users. I discuss the beliefs and perceptions about the future of scenario creators and scenario users, and argue that they should be explicitly addressed before an investigation is undertaken in order to avoid methodological biases in the creation of the scenarios and misunderstanding of the results. As part of this discussion, the basic features of a scenario-based study are reviewed, and applications to landscape and environmental planning are considered, with examples drawn from two studies that were focused on the same concerns and in the same region but which employed different kinds of scenarios.

Energy and Environmental Aspects of Using Corn Stover for Fuel Ethanol - Sheehan, John; Aden, Andy; Paustian, Keith; Killian, Kendrick; Brenner, John; Walsh, Marie; Nelson, Richard (Journal of Industrial Ecology, 2003)
Keywords: agricultural residues biofuels biomass E85 life-cycle assessment (LCA) soil organic carbon (SOC)

Energy balance for ethyl alcohol production from crops - Silva, D. A.; Serra, G. E.; Moreira, J. R.; Concalves, J. C.; Goldemberg, J. (Science, 1978)

Long-term decline of global atmospheric ethane concentrations and implications for methane - Simpson, I. J.; Sulbaek Andersen, M. P.; Meinardi, S.; Bruhwiler, L.; Blake, N. J.; Helmig, D.; Rowland, F. S.; Blake, D. R. (Nature, 2012)
Keywords: Atmosphere/*chemistry Biofuels/utilization Biomass Ethane/*analysis/*chemistry/history Greenhouse Effect History, 20th Century History, 21st Century Methane/*analysis/*chemistry/history Natural Gas/utilization Oil and Gas Fields Ozone/chemistry Wetlands

Made in America, Again. Why Manufacturing Will Return to the U.S. - Sirkin, Harold L.; Zinser, Michael; Hohner, Douglas (BCG Perspectives, 2011)

Will AC Put a Chill on the Global Energy Supply? - Sivak, M. (American Scientist, 2013)
199uw Times Cited:10 Cited References Count:8

Global Challenges and Strategies for Control, Conversion and Utilization of CO2 for Sustainable Development Involving Energy, Catalysis, Adsorption and Chemical Processing - Song, Chunshan (Catalysis Today, 2006)
Keywords: Carbon dioxide Strategy Sustainable development Atom efficiency Utilization energy Tri-reforming CO reforming Emissions Catalysis Conversion Capture Separation Reforming Dimethylcarbonate Supercritical CO Fuels

CANSIM Table 404-0012: Railway Transport Survey, Diesel Fuel Consumption, Annual - Statistics Canada (Government of Canada, 2016)

Emission pathways to achieve 2.0 degrees C and 1.5 degrees C climate targets - Su, X. M.; Takahashi, K.; Fujimori, S.; Hasegawa, T.; Tanaka, K.; Kato, E.; Shiogama, H.; Masui, T.; Emori, S. (Earths Future, 2017)
We investigated the feasibilities of 2.0 degrees C and 1.5 degrees C climate targets by considering the abatement potentials of a full suite of greenhouse gases, pollutants, and aerosols. We revised the inter-temporal dynamic optimization model DICE-2013R by introducing three features as follows. First, we applied a new marginal abatement cost curve derived under moderate assumptions regarding future socioeconomic development-the Shared Socioeconomic Pathways 2 (SSP2) scenario. Second, we addressed emission abatement for not only industrial CO2 but also land-use CO2, CH4, N2O, halogenated gases, CO, volatile organic compounds, SOx, NOx, black carbon and organic carbon. Third, we improved the treatment of the non-CO2 components in the climate module based on MAGICC 6.0. We obtained the following findings: (1) It is important to address the individual emissions in an analysis of low stabilization scenarios because abating land-use CO2, non-CO2 and aerosol emissions also contributes to maintaining a low level of radiative forcing and substantially affects the climate costs. (2) The 2.0 degrees C target can be efficiently reached under the assumptions of the SSP2 scenario. (3) The 1.5 degrees C target can be met with early deep cuts under the assumption of a temperature overshoot, and it will triple the carbon price and double the mitigation cost compared with the 2.0 degrees C case.
Fa5hs Times Cited:7 Cited References Count:54
Keywords: 2 degrees-C land-use air-pollution mitigation scenarios policy energy model CO2 representation

Offshoring and Reshoring: U.S. Insights and Research Challenges - Tate, Wendy L. (Journal of Purchasing and Supply Management, 2014)
Keywords: Offshoring Reshoring In-sourcing Location decision

A multi-criteria based review of models that predict environmental impacts of land use-change for perennial energy crops on water, carbon and nitrogen cycling - Thomas, Amy R. C.; Bond, Alan J.; Hiscock, Kevin M. (GCB Bioenergy, 2013)
Keywords: energy crops GHG emission model Land-use change model selection multi-criteria based decision analysis N2O

Energy. Beneficial biofuels--the food, energy, and environment trilemma - Tilman, D.; Socolow, R.; Foley, J. A.; Hill, J.; Larson, E.; Lynd, L.; Pacala, S.; Reilly, J.; Searchinger, T.; Somerville, C.; Williams, R. (Science, 2009)
Keywords: Biomass Crops, Agricultural Ecosystem *Energy-Generating Resources *Environment *Food *Industrial Waste Plants Politics Public Policy Trees Waste Products Wood

Reconciling energy efficiency and energy intensity metrics: An integrated decomposition analysis - Torrie, Ralph D.; Stone, Christopher; Layzell, David B. (Energy Efficiency, 2018)

G20 Subsidies to Oil, Gas and Coal Production: Canada - Touchette, Yanick (Overseas Development Institute, UK, Oil Change International (Washington, DC) and International Institute for Sustainable Development (CA), 2015)

Transportation in Canada, 2014 - Transport Canada (Canada: Minister of Transport, 2015)

Population Estimates - U.S. Census (2016)

2016 Top Markets Report Renewables Fuels, Country Cast Study: Mexico - U.S. DOC (U.S. Department of Commerce International Trade Administration, 2016)

Transportation Energy Data Book, Appendix A, Tables A.13-A.16; Table A.09 - U.S. DOE (U.S. Department of Energy, 2014)

Transportation Energy Data Book, Appendix A.09 - U.S. DOE (U.S. Department of Energy, 2014)

Quadrennial Technology Review, An Assessment of Energy Technologies and Research Opportunities - U.S. DOE (U.S. Department of Energy, 2015)

Appliance Standards Fact Sheet - U.S. DOE (U.S. Department of Energy, 2017)

2016 Wind Technologies Market Report - U.S. DOE (U.S. Departmenrt of Energy Office of Energy Efficiency and Renewable Energy, 2017)

2016–2020 Strategic Plan and Implementing Framework - U.S. DOE (U.S. Department of Energy Office of Energy Efficiency and Renewable Energy, 2015)

Summary of Fuel Economy Performance - U.S. DOT (U.S. Department of Transportation, 2016)

Cost-Effective Directed Inspection and Maintenance Control Opportunities At Five Gas Processing Plants and Upstream Gathering Compressor Stations and Well Sites - U.S. EPA (U.S. Environmental Protection Agency. Prepared by National Gas Machinery Laboratory; Clearstone Engineering & Innovative Environmental Solutions, 2006)

Clean Energy-Environment Guide to Action: Policies, Best Practices, and Action Steps for States - U.S. EPA (U.S. Environmental Protection Agency, 2006)

Inventory of U.S. Greenhouse Gas Emissions and Sinks: 1990-2011. EPA 430-R-13-004 - U.S. EPA (U.S. Environmental Protection Agency, 2013)

Inventory of U.S. Greenhouse Gas Emissions and Sinks: 1990-2012. EPA 430-R-14-003 - U.S. EPA (U.S. Environmental Protection Agency, 2014)

Inventory of U.S. Greenhouse Gas Emissions and Sinks: 1990-2013. EPA 430-R-15-004 - U.S. EPA (U.S. Environmental Protection Agency, 2015)

Climate Change in the United States: Benefits of Global Action. EPA 430-R-15-001 - U.S. EPA (U.S. Environmental Protection Agency, Office of Atmospheric Programs, 2015)

Inventory of U.S. Greenhouse Gas Emissions and Sinks: 1990–2014. EPA 430-R-16-002 - U.S. EPA (U.S. Environmental Protection Agency, 2016)

Inventory of U.S. Greenhouse Gas Emissions and Sinks: 1990-2015 - U.S. EPA (U.S. Environmental Protection Agency, 2017)

Greenhouse Gas Emission Baselines and Reduction Potential From Buildings in Mexico - UNEP (United Nations Environment Programme, 2009)

Production Tax Credit for Renewable Energy - Union of Concerned Scientists (2014)

Canada Biofuels Annual 2015 - USDA Foreign Agricultural Service GAIN (U.S. Department of Agriculture, Global Agricultural Information Network, 2015)

Scenarios and Forecasting: Two Perspectives - Van Der Heijden, Kees (Technological Forecasting and Social Change, 2000)

An updated scenario typology - van Notten, Philip W. F.; Rotmans, Jan; van Asselt, Marjolein B. A.; Rothman, Dale S. (Futures, 2003)

Combining backcasting and exploratory scenarios to develop robust water strategies in face of uncertain futures - van Vliet, Mathijs; Kok, Kasper (Mitigation and Adaptation Strategies for Global Change, 2015)
Water management strategies in times of global change need to be developed within a complex and uncertain environment. Scenarios are often used to deal with uncertainty. A novel backcasting methodology has been tested in which a normative objective (e.g. adaptive water management) is backcasted within the context of exploratory scenarios that sketch four different plausible futures (Economy First, Policy Rules, Fortress Europe, and Sustainability Eventually). The main advantage of combining exploratory and normative scenarios is in the identification of robust actions: actions that are effective in the different socio-environmental contexts sketched in the exploratory scenarios. This paper has three objectives: (1) to present the methodology, focussing on its novel aspects (2) to test the methodology and evaluate its perceived success by analysing organiser and stakeholder feedback and (3) to analyse and evaluate the results, in order to study the impact of the exploratory scenarios on the backcasting results and the added value of robust actions. The methodology was successfully tested in 9 local and one regional case study in a water project water scenarios for Europe and for Neighbouring States (SCENES). Results showed that the exploratory scenarios influenced the content of the backcasts, thus making the identification of robust strategies possible. The list of robust strategies includes both technological and social/organisational strategies, highlighting the need for an integrated approach. The approach shows high potential, but as the methodology is in its infancy more research is needed, particularly in methods to facilitate and monitor information flow between exploratory scenarios and backcasts.

Power-generation System Vulnerability and Adaptation to Changes in Climate and Water resources - van Vliet, Michelle T. H.; Wiberg, David; Leduc, Sylvain; Riahi, Keywan (Nature Climate Change, 2016)

Accommodating or compromising change? A story about ambitions and historic deterministic scenarios - van’ t Klooster, Susan A.; van Asselt, Marjolein B. A. (Futures, 2011)
Keywords: Foresight (in action) Accommodating change Temporal repertoires Historic determinism Futuristic difference

Energy and greenhouse gas emission effects of corn and cellulosic ethanol with technology improvements and land use changes - Wang, Michael Q.; Han, Jeongwoo; Haq, Zia; Tyner, Wallace E.; Wu, May; Elgowainy, Amgad (Biomass and Bioenergy, 2011)

Ward's World Motor Vehicle Data 2015 - WardsAuto (WardsAuto, 2015)

Putting Renewables and Energy Efficiency to Work: How Many Jobs Can the Clean Energy Industry Generate in the US? - Wei, Max; Patadia, Shana; Kammen, Daniel M. (Energy Policy, 2010)
Keywords: Green jobs Renewable energy employment Energy efficiency employment

Stimulus Package Worth $35B - Whittington, Les; Campion-Smith, Bruce (The Star (Toronto), 2009)

Effects of Climate Change on Energy Production and Use in the United States - Wilbanks, Thomas J.; Vatsal Bhatt; Daniel E. Bilello; Stanley R. Bull; James Ekmann, W; illiam C. Horak; Y. Joe Huang; Mark D. Levine; Michael J. Sale; David K.Schmalzer; Scott, Michael J. (U.S. Climate Science Program and the subcommittee on Global Change Research, 2007)

World DataBank - World Bank (World Bank Group, 2016)

World Development Indicators - World Bank (World Bank Group, 2016)

The Little Data Book on Private Sector Development 2016 - World Bank (World Bank Group, 2016)

World Energy Resources 2016 Report - World Energy Council (World Energy Council, 2016)

CAIT Climate Data Explorer - World Resources Institute (2016)

Reconciling Divergent Estimates of Oil and Gas Methane Emissions - Zavala-Araiza, D.; Lyon, D. R.; Alvarez, R. A.; Davis, K. J.; Harriss, R.; Herndon, S. C.; Karion, A.; Kort, E. A.; Lamb, B. K.; Lan, X.; Marchese, A. J.; Pacala, S. W.; et al. (Proceedings of the National Academy of Sciences USA, 2015)
Keywords: Barnett Shale greenhouse gas footprint methane emissions natural gas supply chain oil and gas emissions

Mexico Hopes Transportation Upgrades Will Accommodate Expanded Oil, Gas Supply - Zborowski, Matt (Oil and Gas Journal, 2015)

Modeling the Effect of Climate Change on U.S. State-level Buildings Energy Demands in An Integrated Assessment Framework - Zhou, Yuyu; Clarke, Leon; Eom, Jiyong; Kyle, Page; Patel, Pralit; Kim, Son H.; Dirks, James; Jensen, Erik; Liu, Ying; Rice, Jennie; Schmidt, Laurel; Seiple, Timothy (Applied Energy, 2014)
Keywords: Buildings energy demand Electricity use Climate change Integrated assessment model Sensitivity

The Effect of Global Climate Change, Population Distribution, and Climate Mitigation on Building Energy Use in the U.S. and China - Zhou, Yuyu; Eom, Jiyong; Clarke, Leon (Climatic Change, 2013)

Indirect land use change: Much ado about (almost) nothing - Zilberman, David (GCB Bioenergy, 2017)

Methane Emissions From the Natural Gas Transmission and Storage System in the United States - Zimmerle, D. J.; Williams, L. L.; Vaughn, T. L.; Quinn, C.; Subramanian, R.; Duggan, G. P.; Willson, B.; Opsomer, J. D.; Marchese, A. J.; Martinez, D. M.; Robinson, A. L. (Environmental Science and Technology, 2015)
Keywords: Air Pollutants/*analysis Greenhouse Effect Methane/*analysis Models, Theoretical Natural Gas/*analysis United States

America’s Pledge Phase 1 Report: States, Cities, and Businesses in the United States Are Stepping Up on Climate Action - America’s Pledge (America’s Pledge Project, 2017)

Pathways to Deep Decarbonization in Canada - Bataille, C.; Chan, J.; Sawyer, D.; Adamson, R. (Sustainable Development Solutions Network and Institute for Sustainable Development and International Relations, 2014)

Pathways to Deep Decarbonization in Canada - Bataille, C.; Sawyer, D.; Melton, N. (Sustainable Development Solutions Network and Institute for Sustainable Development and International Relations, 2015)

Drivers, Trends and Mitigation - Blanco, G.; Gerlagh, R.; Suh, S.; Barrett, J.; de Coninck, H.C.; Diaz Morejon, C. F.; Mathur, R.; Nakicenovic, N.; Ofosu Ahenkora, A.; Pan, J.; Pathak, H.; Rice, J.; et al. (Climate Change 2014: Mitigation of Climate Change. Contribution of Working Group III to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change, 2014)

Advanced Nuclear Energy: Need, Characteristics, Project Costs and Opportunities - CATF (Clean Air Task Force, 2018)

Sankey Diagrams Associated With Fuel and Electricity Production and Use in Canada - CESAR (Canadian Energy Systems Analysis Research, 2018)

CARMA Database of Power Plants - CGD (Carbon Monitoring for Action, Center for Global Development, 2012)

Country comparison: Electricity: Installed generating capacity - CIA (The World Factbook, 2018)

The Two Sides of the Paris Climate Agreement: Dismal Failure or Historic Breakthrough? - Clémençon, Raymond (Journal of Environment and Development, 2016)

Green Building in North America: Opportunities and Challenges. Secretariat Report to Council Under Article 13 of the North American Agreement on Environmental Cooperation - Commission for Environmental Cooperation (2008)

Pathways to Deep Decarbonization 2015 Report Executive Summary - Deep Decarbonization Pathways Project (Sustainable Development Solutions Network and Institute for Sustainable Development and International Relations, 2015)

Energy Supply and Use - Dell, J.; Tierney, S.; Franco, G.; Newell, R. G.; Richels, R.; Weyant, J.; Wilbanks, T. J. (Climate Change Impacts in the United States: The Third National Climate Assessment, 2014)

Progress Towards Canada’s Greenhouse Gas Emissions Reduction Target - ECCC (Environment and Climate Change Canada, 2017)

Emissions of Greenhouse Gases in the United States 2009 Report - EIA (U.S. Energy Information Administration, 2011)

Annual Energy Outlook 2013 With Projections to 2040. DOE/EIA-0383(2013) - EIA (U.S. Energy Information Administration, 2013)

Electric Power Annual 2015 Report - EIA (U.S. Energy Information Adminstration, 2016)

Country Analysis Brief: Mexico - EIA (U.S. Energy Information Administration, 2016)

Coal made up more than 80% of retired electricity generating capacity in 2015 - EIA (Today in Energy, 2016)

International Energy Statistics - EIA (U.S. Energy Information Administration, 2017)

EIA adds small-scale solar photovoltaic forecasts to its monthly Short-Term Energy Outlook - EIA (Today in Energy, 2017)

More than half of small-scale photovoltaic generation comes from residential rooftops - EIA (Today in Energy, 2017)

Renewable Energy Explained - EIA (U.S. Energy Information Administration, 2018)

Nearly half of utility-scale capacity installed in 2017 came from renewables - EIA (Today in Energy, 2018)

Almost all power plants that retired in the past decade were powered by fossil fuels - EIA (Today in Energy, 2018)

Electric Power Annual 2016 Report - EIA (U.S. Energy Information Administration, 2018)

U.S. carbon dioxide emissions from energy consumption (from 1973) - EIA (U.S. Energy Information Administration, 2018)

Annual Energy Outlook, 2018 with Projections to 2050 Report - EIA (U.S. Energy Information Administration, 2018)

Statement by President Trump on the Paris Climate Accord - Executive Office of the President (2017)

Issues related to mitigation in the long term context - Fisher, B. S.; Nakicenovic, N.; Alfsen, K.; Corfee Morlot, J.; de la Chesnaye, F.; Hourcade, J.-Ch.; Jiang, K.; Kainuma, M.; La Rovere, E.; Matysek, A.; Rana, A.; Riahi, K.; et al. (Climate Change 2007: Mitigation. Contribution of Working Group III to the Fourth Assessment Report of the Intergovernmental Panel on Climate Change, 2007)

Financing Mexico's next infrastructure wave - Goebel, H. P.; Schwandt, G. A. (International Financial Law Review, 2013)

Energy Primer - Grubler, A.; Johansson, T. B.; Mundaca, L.; Nakicenovic, N.; Pachauri, S.; Riahi, K.; Rogner, H.-H.; Strupeit, L. (Global Energy Assessment - Toward a Sustainable Future, 2012)

Nuclear Power Review 2017 - IAEA (International Atomic Energy Agency, 2017)

World Energy Balances - IEA (IEA World Energy Statistics and Balances (database), 2017)

“Net electrical capacity” and “Electricity and heat generation.” - IEA (International Energy Agency, 2017)

World Energy Outlook 2017 - IEA (International Energy Agency, 2017)

Renewables 2017: Analysis and Forecasts to 2022 - IEA (International Energy Agency, 2017)

OECD - Net Capacity of Renewables - IEA (IEA Renewables Information Statistics (database), 2018)

National Accounts Selected Indicators - IMF (International Monetary Fund, 2016)

Summary for Policymakers - IPCC (IPCC Special Report on Renewable Energy Sources and Climate Change Mitigation, 2011)

Renewable Power Generation Costs in 2017 - IRENA (International Renewable Energy Agency, 2018)

Renewable Energy and Jobs, Annual Review 2018 - IRENA (International Renewable Energy Agency, 2018)

Energy Flow Charts - Lawrence Livermore National Laboratory (U.S. Department of Energy Lawrence Livermore National Laboratory, 2018)

Soft Energy Paths: Toward a Durable Peace - Lovins, A. (Friends of the Earth International/Ballinger Publishing Company, 1977)

Renewable Electricity Futures for the United States - Mai, Trieu; Hand, M. Maureen; Baldwin, Samuel F.; Wiser, Ryan H.; Brinkman, Greg L.; Denholm, Paul; Arent, Doug J.; Porro, Gian; Sandor, Debra; Hostick, Donna J.; Milligan, Michael; DeMeo, Edgar A.; et al. (IEEE Transactions on Sustainable Energy, 2014)

Energy, Industry, and Waste Management Activities: An Introduction to CO2 Emissions From Fossil Fuels - Marland, G.; Andres, R. J.; Blasing, T. J.; Boden, T. A.; Broniak, C. T.; Gregg, J. S.; Losey, L. M.; Treanton, K. (First State of the Carbon Cycle Report (SOCCR): The North American Carbon Budget and Implications For the Global Carbon Cycle. a Report By the U.S. Climate Change Science Program and the Subcommittee on Global Change Research, 2007)

U.S. Energy Scenarios for the 21st Century - Mintzer, I.; Leonard, J. A.; Schwartz, P. (Pew Center on Global Climate Change, 2003)

Energy Efficiency in the United States: 35 Years and Counting - Nadel, S.; Elliott, N.; Langer, T. (Research Report E1502, American Council for an Energy Efficient Economy, 2015)

Residential Housing Stock and Floor Space - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2018)

Residential Secondary Energy Use (Final Demand) by Energy Source and End Use - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2018)

Industrial Secondary Energy Use and GHG Emissions by Energy Source - Natural Resources Canada (Government of Canada, Ministry of Natural Resources, 2018)

The Role of Nuclear Energy in a Low-Carbon Energy Future - NEA (OECD Nuclear Energy Agency, 2012)

Drivers of ecosystem change: Summary chapter - Nelson, G. C. (Ecosystems and Human Well-Being: Current State and Trends, Volume 1, 2005)

The Climate Casino: Risk, Uncertainty, and Economics for a Warming World - Norhaus, W. (Yale University, 2013)

Climate Change and Indigenous Peoples: A Synthesis of Current Impacts and Experiences. General Technical Report PNWGTR-944 - Norton-Smith, K.; Lynn, K.; Chief, K.; Cozzetto, K.; Donatuto, J.; Redsteer, M. H.; Kruger, L. E.; Maldonado, J.; Viles, C.; Whyte, K.P. (U.S. Department of Agriculture, Forest Service, Pacific Northwest Research Station, 2016)

Renewable Electricity Futures Study. NREL/TP-6A20-52409 - NREL (U.S. Department of Energy National Renewable Energy Laboratory, 2012)

The Energy to Lead, 2015, New York State Energy Plan - NYSERDA (New York State Energy Planning Board, 2015)

How to spend a dwindling greenhouse gas budget - Obersteiner, Michael; Bednar, Johannes; Wagner, Fabian; Gasser, Thomas; Ciais, Philippe; Forsell, Nicklas; Frank, Stefan; Havlik, Petr; Valin, Hugo; Janssens, Ivan A.; Peñuelas, Josep; Schmidt-Traub, Guido (Nature Climate Change, 2018)

On the Path to SunShot: Emerging Issues and Challenges in Integrating Solar with the Distribution System. NREL/TP-5D00-65331 - Palmintier, Bryan; Broderick, Robert; Mather, Barry; Coddington, Michael; Baker, Kyri; Ding, Fei; Reno, Matthew; Lave, Matthew; Bharatkumar, Ashwini (U.S. Department of Energy, National Renewable Energy Laboratory, 2016)

Backcasting for a Sustainable Future: The Impact After Ten Years - Quist, J. (Eburon Publishers, 2007)

Backcasting and scenarios for sustainable technology development - Quist, J. (Handbook of Sustainable Engineering, 2013)

Ecosystems and Human Well-being: Synthesis - Reid, W. V.; Mooney, H. A.; Cropper, A.; Capistrano, D.; Carpenter, S. R.; Chopra, K.; Dasgupta, P.; Dietz, T.; Duraiappah, A. K.; Hassan, R.; Kasperson, R.; Leemans, R.; et al. (Island Press, 2005)

Paris Agreement climate proposals need a boost to keep warming well below 2 degrees C - Rogelj, J.; den Elzen, M.; Hohne, N.; Fransen, T.; Fekete, H.; Winkler, H.; Schaeffer, R.; Sha, F.; Riahi, K.; Meinshausen, M. (Nature, 2016)
The Paris climate agreement aims at holding global warming to well below 2 degrees Celsius and to "pursue efforts" to limit it to 1.5 degrees Celsius. To accomplish this, countries have submitted Intended Nationally Determined Contributions (INDCs) outlining their post-2020 climate action. Here we assess the effect of current INDCs on reducing aggregate greenhouse gas emissions, its implications for achieving the temperature objective of the Paris climate agreement, and potential options for overachievement. The INDCs collectively lower greenhouse gas emissions compared to where current policies stand, but still imply a median warming of 2.6-3.1 degrees Celsius by 2100. More can be achieved, because the agreement stipulates that targets for reducing greenhouse gas emissions are strengthened over time, both in ambition and scope. Substantial enhancement or over-delivery on current INDCs by additional national, sub-national and non-state actions is required to maintain a reasonable chance of meeting the target of keeping warming well below 2 degrees Celsius.
Rogelj, Joeri den Elzen, Michel Hohne, Niklas Fransen, Taryn Fekete, Hanna Winkler, Harald Schaeffer, Roberto Sha, Fu Riahi, Keywan Meinshausen, Malte eng Research Support, Non-U.S. Gov't England 2016/07/01 06:00 Nature. 2016 Jun 30;534(7609):631-9. doi: 10.1038/nature18307.
Keywords: Carbon Dioxide/analysis Confounding Factors (Epidemiology) Environmental Policy/*legislation & jurisprudence/*trends Global Warming/*legislation & jurisprudence/*prevention & control *Goals Greenhouse Effect/legislation & jurisprudence/prevention & control International Cooperation/*legislation & jurisprudence Paris *Temperature Time Factors Uncertainty

Human drivers of national greenhouse-gas emissions - Rosa, Eugene A.; Dietz, Thomas (Nature Climate Change, 2012)

Small Modular Reactors - Key to Future Nuclear Power Generation in the U.S. - Rosner, R.; Goldberg, S. (Energy Policy Institute at Chicago, University of Chicago, 2011)

New Lens Scenarios: A Shift in Perspective for a World in Transition - Royal Dutch Shell (2013)

The World Nuclear Industry Status Report - Schneider, M.; Froggat, A.; Hazemann, J.; Katsuta, T.; Ramana, M. V.; Rodriquez, J. C.; Rudinger, A.; Stienne, A. (Mycle Schneider Consulting Project, 2017)

The Grand Challenges in Carbon Capture, Utilization, and Storage - Smit, Berend; Park, Ah-Hyung Alissa; Gadikota, Greeshma (Frontiers in Energy Research, 2014)

Summary for policymakers - Stocker, T. F.; Dahe, Q.; Plattner, G. K. (Climate Change 2013: The Physical Science Basis. Contribution of Working Group I to the Fifth Assessment Report of the Intergovernmental Panel on Climate Change, 2013)

Construction of Most Nuclear-Power Reactors is Behind Schedule - The Economist (The Economist Group Limited, 2017)

President Obama on Climate and Energy, A Historic Commitment to Protecting the Environment and Addressing the Impacts of Climate Change - The Record (2016)

Understanding energy systems change in Canada: 1. Decomposition of total energy intensity - Torrie, Ralph D.; Stone, Christopher; Layzell, David B. (Energy Economics, 2016)

Pathways to Deep Decarbonization in Mexico, MX 2015 Report - Tovilla, J.; (eds.), D. Buira (Sustainable Development Solutions Network and Institute for Sustainable Development and International Relations, 2015)

Quadrennial Energy Review: Energy Transmission, Storge and Distribution Infrastructure - U.S. DOE (U.S. Department of Energy, 2015)

Basic Research Needs for Future Nuclear Energy - U.S. DOE (U.S. Department of Energy, Office of Science, 2017)

Quadrennial Energy Review — Transforming the Nation’s Electricity System: The Second Installment of the QER - U.S. DOE (Quadrennial Energy Review Task Force, 2017)

Summary of Fuel Economy Performance (Public Version), NHTSA, NVS-220 - U.S. DOT (U.S. Department of Transportation, 2014)

Environmental Protection Agency, 40 CFR Parts 85, 86 and 600, Department of Transportation, National Highway Traffic Safety Administration, 49 CFR Parts 523, 531, 533, 536 and 537, Federal Register, 77(199): 62624-63200 - U.S. EPA and U.S. DOT (2012)

The Benefits and Costs of the Clean Air Act from 1990 to 2020, Final Report – Rev. A - U.S. EPA (U.S. Environmental Protection Agency, 2011)

Energy Star® Overview of 2015 Achievements - U.S. EPA (U.S. Environmental Protection Agency, 2015)

Multi-Model Framework for Quantitative Sectoral Impact Analysis, A Technical Report for the Fourth National Climate Assessment - U.S. EPA (U.S. Environmental Protection Agency, 2017)

Country Market Brief - U.S. Green Building Council (2016)

World Population Prospects: The 2015 Revision - UN (United Nations, 2015)

United Nations Framework Convention on Climate Change, Paris Agreement - UNFCCC (2015)

United States Mid-Century Strategy for Deep Decarbonization - White House (2016)

Policy Implications of Deep Decarbonization in the United States - Williams, J. H.; Haley, B.; Jones, R. (The U.S. report of the Deep Decarbonization Pathways Project of the Sustainable Development Solutions Network and the Institute for Sustainble Development and International Relations, San Francisco, 2015)

Pathways to Deep Decarbonization in the United States - Williams, J. H.; Haley, B.; Kahrl, F.; Moore, J.; Jones, A. D.; Torn, M. S.; McJeon, H. (The U.S. report of the Deep Decarbonization Pathways Project of the Sustainable Development Solutions Network and the Institute for Sustainble Development and International Relations, San Francisco, 2014)

World Bank Indicators - World Bank (World Bank Group, 2017)

World Bank Indicators, World Bank National Accounts Data, and OECD National Accounts Data Files - World Bank (World Bank Group, 2018)

World Energy Resources 2013 Survey - World Energy Council (World Energy Council, 2013)

World Energy Scenarios, 2016: The Grand Transition - World Energy Council (2016)

Current and Future Generation - World Nuclear Association (2018)